2022
DOI: 10.1002/slct.202103470
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Synthesis of Biologically Active Cyclodepsipeptides

Abstract: Cyclodepsipeptide are a class of natural cyclic peptides that have a wide range of biological activities, hence the potential to be developed as new drug candidates. Cyclodpesipeptides comprise a backbone of amide bonds and at least one ester moiety, thus are complex and challenging to synthesis. Generally, cyclodepsipeptides are synthesised via solid‐phase peptide synthesis, solution‐phase or a combination of solid and solution‐phase. Currently, solid‐phase peptide synthesis is more in demand, but it also has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
(191 reference statements)
1
5
0
Order By: Relevance
“…The traditional Yamaguchi reaction conditions required more than 12 h longtime slow dropwise addition to dilute the reaction concentration, but due to the intensely enhanced mass transfer under flow conditions, the operational process under flow conditions was simplified for easy pumping into the reaction coil. The 1 H NMR, 13 C NMR, and mass spectra of flow synthesized 4 and 5 were found to be completely identical to those of natural products in the literature 44 (Tables S-6 and S-7, ESI †).…”
Section: Flow Macrolactamization Of An N-methylated Amine (-Conr 2 )supporting
confidence: 55%
See 1 more Smart Citation
“…The traditional Yamaguchi reaction conditions required more than 12 h longtime slow dropwise addition to dilute the reaction concentration, but due to the intensely enhanced mass transfer under flow conditions, the operational process under flow conditions was simplified for easy pumping into the reaction coil. The 1 H NMR, 13 C NMR, and mass spectra of flow synthesized 4 and 5 were found to be completely identical to those of natural products in the literature 44 (Tables S-6 and S-7, ESI †).…”
Section: Flow Macrolactamization Of An N-methylated Amine (-Conr 2 )supporting
confidence: 55%
“…10,11 It is well known that the macrocyclization step is the key step in cyclodepsipeptide synthesis, especially in the macrolactamization of N-alkylated amino acids (N-methyl amino acids or proline) 12 and in macrolactonization. 13,14 It has been reported that the macrolactamization of N-alkylated amino acids has the potential to introduce cis-amide bonds into peptides and results in a turninducing isomer, 15,16 and the lower nucleophilicity of N-alkylated amine and hydroxy also leads to a lower yield of macrocyclization compared to the primary amine case. On the other hand, a sterically hindered amino acid will also affect the yield of linear precursors via solid-phase peptide synthesis (SPPS).…”
Section: Introductionmentioning
confidence: 99%
“… 5,6 Therefore, the development of new anticancer agents as alternatives to the currently available therapies is necessary to resolve the side-effect problems. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Most cyclic peptides are prepared via solid-phase peptide synthesis (SPPS) of the linear precursor, continued by macrocyclization on-resin or in solution [10]. The efficiency of the solution and on-resin cyclization were compared extensively by Sewald and colleagues [11] for the synthesis of cyclopeptides and cyclohexapeptides.…”
Section: ■ Introductionmentioning
confidence: 99%